Bring students together to create strong bonds to your university. Issue 6 (22nd January 2018) - Sutton, Halley
Abstract : Jerry Price, Ph.D., first became invested in student affairs as a graduate resident advisor. As dean of student affairs at Chapman University, Price has helped boost his institution's first‐to‐second‐year retention rate from 86 percent to a consistent retention rate in the low‐to‐mid‐90‐percent range. He shared strategies for increasing first‐year retention, as well as for facilitating an atmosphere of critical thinking when tackling tricky topics on campus.